The effect of ginsenoside Rg3 combined with chemotherapy on immune function in non-small cell lung cancer: A systematic review and meta-analysis of randomized controlled trials. Issue 14 (7th April 2023) - Gao, Song; Fang, Cancan; Wang, Tiancheng; Lu, Wenjie; Wang, Nan; Sun, Lingfeng; Fang, Wenyou; Chen, Yang; Hu, Rongfeng
Abstract : Background: The occurrence and development of non-small cell lung cancer (NSCLC) are closely related to the immune status of the tumor-host. The immunosuppression caused by tumor cells and toxic side effects produced by chemotherapeutic drugs results in a decrease in immune function, ultimately leading to the failure of clinical chemotherapy treatment. Ginsenoside Rg3 has been clinically reported to have positive effects in enhancing immune function in patients. Thus, we screened and evaluated the quality of the evidence regarding the benefits of ginsenoside Rg3 and conducted a meta-analysis to assess the impact on improving immune function in NSCLC. Methods: The PubMed, EMBASE, Cochrane Library, CNKI, Weipu (VIP), and Wanfang databases were searched in this study, all from the time of library construction to January 2023. Results: In total, 12 trials with a sample size of 1008 cases were included based on the eligible criteria. The results showed that compared with first-line chemotherapy alone, the combination of ginsenoside Rg3 and first-line chemotherapy could better improve level of the CD3 + T lymphocytes [mean difference (MD) = 4.72; 95% confidence intervals (CI): 3.92, 5.53; P < .00001], CD4 + T lymphocytes (MD = 4.93; 95% CI: 4.61, 5.26; P < .00001), CD8 + T lymphocytes (MD = 2.67; 95% CI: 0.93, 4.37; P = .003), CD4 + /CD8 + T lymphocytes (MD = 0.20; 95% CI: 0.09, 0.32; P = .0006), increase the activity of nature killer cells (MD = 2.11; 95% CI: 0.58, 3.63; P = .007), recover the decline of the white blood cell count induced by chemotherapy, and improve the clinical efficacy for patients. Conclusion: This study confirmed that ginsenoside Rg3 has some efficacy advantages for improving immune function in patients with NSCLC.